Modification on Recycled Aggregates and its Influence on Recycled Concrete. (August 2019) - Huang, K; Ding, T; Xiao, J; Singh, A
Abstract: Recycled aggregates produced from waste concrete are widely accepted as green building material. However, demolition processes will bring recycled aggregates with a lower apparent density, bulk density whereas a higher porosity, silt content, water absorption, crushing index value when compared with natural aggregates. So the strengthening and modification of recycled aggregates have become a prominent technological issue in the producing process. This paper introduces current modification methods on the recycled aggregates, which mainly include: (1) physical technology, its basic idea is to remove the waste cement paste adhered to recycled aggregates, such processions as rubbing, heating, particle shaping, and micro-heating; (2) chemical technology, carried out by immersing recycled aggregates in different kinds of chemical grout, which can be mixed with additive Kim powder, silica fume, fly ash, and any other fine mineral powder or slag; (3) carbonation technology, when newly collected crushed aggregates are put into atmosphere with high CO2 concentration, the adhesive cement paste can react with CO2 and produce CaCO3 that will precipitate in the capillary pores or cracks, which will improve properties of recycled aggregates; (4) nano technology, the use of nanomaterials can promote the hydration reaction, react with cement based materials, fill pores and control the process of crystallization. Conclusions are put forward and several problems concerning modification need to be considered for further research and application are proposed and discussed. Compared with natural concrete, RAC is superior to environmental value in the reduction of CO2 emission in Life Cycle Assessment.